KONDUKTIVITAS PANAS DAN KOEFISIEN PINDAH PANAS PADA PROSES PENGERINGAN GABAH DENGAN MENGGUNAKAN CABINET DRYER - Rusli, Riska; Jamaluddin P, Jamaluddin P; Yanto, Subari (Universitas Negeri Makassar, 2018)
The purpose of this research is to know the conductivity and coefficient of heat transfer in drying process of gabah (unhulled rice) by using cabinet dryer. This research is a type of experimental research done by drying